2017
DOI: 10.1097/tp.0000000000001738
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Outcomes of MELD ≥ 40 Liver Transplantation

Abstract: Implementation of the Share 35 allocation policy has a significant effect on outcomes by improving organ access and minimizing candidate waiting times. Recipients achieving a MELD of 40 or higher at our center post-Share 35 had an improved 1-year graft survival. However, nearly 40% remained hospitalized for more than 4 weeks posttransplant, and 20% were discharged to an acute care facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…As the UK moves to an organ allocation system based on wait list mortality it would be interesting to observe the impact on outcomes of patients after this change as those with organ failures will be more likely to receive an offer. In countries where MELD based allocation is already in use(31) it would be interesting to see if the outcomes of patients with cirrhosis and organ failure in general is different to what we report here.…”
Section: Discussioncontrasting
confidence: 62%
“…As the UK moves to an organ allocation system based on wait list mortality it would be interesting to observe the impact on outcomes of patients after this change as those with organ failures will be more likely to receive an offer. In countries where MELD based allocation is already in use(31) it would be interesting to see if the outcomes of patients with cirrhosis and organ failure in general is different to what we report here.…”
Section: Discussioncontrasting
confidence: 62%
“…This has been most readily demonstrated with the early implementation of the model for end-stage liver disease score when some considered the transplantation of those with scores ≥40 to be futile. 35 , 36 Surgeons frequently utilize nonquantifiable judgment, often referred to as the “eye-ball” test aiming to assess the patient’s function, skeletal muscle mass, nutritional status, and global health status and identify patients that will do well posttransplant. Most studies evaluating skeletal muscle mass have used some form of imaging for measurement of skeletal muscle mass, alone or in combination with functional assessment of physical performance or strength.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kwang et al have recently reported a significantly improved 1year survival among patients having MELD scores of 35 or higher compared to those with lower MELD scores, 27 and another study by Nekrasov et al observed improved outcomes in patients with MELD scores of 40 or higher after the implantation of Share 35 policy. 28 Further efforts are recommended to focus on patients with NASH having MELD scores of 35 or higher to improve post-transplantation outcomes.…”
Section: Discussionmentioning
confidence: 99%